Inflammatory Fibroid Polyp Causing Colocolic Intussusception in an Infant - Mark Walton; Juan Bass; Blair Carpenter (Canadian Journal of Gastroenterology)
A three-month-old infant presented to the emergency department with a 24 h history of irritability and lesion prolapsing intermittently per anus. The child had a six-week history of blood and mucus per rectum. Digital rectal examination and sigmoidoscopy revealed what appeared to be a large mobile polypoid lesion arising from the rectum. Plans for excision were made. Sigmoidoscopy performed the following morning failed to demonstrate any lesion in the rectum or sigmoid. Barium enema demonstrated a sessile ‘apple core type’ lesion in the descending colon. Segmental resection of the descending colon with end-to-end anastomosis was performed. Pathological examination of the resected bowel demonstrated features consistent with an inflammatory fibroid polyp. This case appears to be unique because of the young age of the patient, its unusual location and its presentation as an intermittent colocolic intussusception.